2016
DOI: 10.18632/oncotarget.12901
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy for the treatment of thyroid cancer: a pilot study

Abstract: We preliminarily evaluated the clinical feasibility and efficacy of intraoperative radiotherapy in patients with thyroid carcinoma. Nine thyroid cancer patients received intraoperative radiotherapy using an Intrabeam system. The dose was 3-4 Gy and the irradiation time ranged from 1 min 32 s to 7 min 33s. One case was a primary thyroid carcinoma, while the other cases were recurrent disease. Adverse effects, recurrence and survival were analyzed. In one patient, poorly differentiated thyroid carcinoma recurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Due to the heterogeneity of the population included in these studies, large variations were observed in the outcomes, primarily coming from the studies using IOERT. Reported acute and late toxicity rates included wound infection ( n = 20, 9.9%) [ 38 ], vascular [transient ischemic attack (TIA), carotid blowout, cardiac ischaemic events] ( n = 23, 11.3%) [ 38 ], pain needing opiates ( n = 16, 13.3%) [ 34 ], osteoradionecrosis ( n = 4, 17.4%) [ 32 ] and mild nausea/vomiting (55.6%) [ 53 ].…”
Section: Heterogenous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the heterogeneity of the population included in these studies, large variations were observed in the outcomes, primarily coming from the studies using IOERT. Reported acute and late toxicity rates included wound infection ( n = 20, 9.9%) [ 38 ], vascular [transient ischemic attack (TIA), carotid blowout, cardiac ischaemic events] ( n = 23, 11.3%) [ 38 ], pain needing opiates ( n = 16, 13.3%) [ 34 ], osteoradionecrosis ( n = 4, 17.4%) [ 32 ] and mild nausea/vomiting (55.6%) [ 53 ].…”
Section: Heterogenous Studiesmentioning
confidence: 99%
“…Acute toxicities reported were wound infection/dehiscence in 1.6%–54% of patients [ 8 , 10 , 14 , 16 , 18 , 19 , 22 , 27 , 34 , 36 39 , 41 , 48 , 51 53 , 55 , 59 ], necrosis or flap failure in 0.7%–23% [ 14 , 16 , 18 , 23 , 26 , 28 30 , 38 , 39 , 52 , 55 , 59 ], osteonecrosis in 1.1%–8% [ 20 , 22 , 36 , 38 , 39 , 41 , 44 , 45 , 50 ], fistula in 1.5%–20% [ 8 , 10 , 14 , 16 , 18 20 , 24 26 , 30 , 31 , 33 , 34 , 37 39 , 41 , 44 , 46 , 52 , 53 , 59 ], trismus in 4.5%–24.6% [ 24 , 25 , 37 ], skin/mucosal complications in 2.3%–100% [ 8 , 10 , 14 16 , 24 , …”
Section: Heterogenous Studiesmentioning
confidence: 99%
“… 80 , 81 , 85 Intraoperative radiotherapy (IORT) permits higher radiation doses without harming healthy tissue but this has not yet been investigated in DTC. 86 …”
Section: External Beam Radiation Therapymentioning
confidence: 99%